Self-Management Counseling and Physical Health Status among Patients with Pulmonary TB in Bogor, Indonesia - Jauhar, Muhamad; Nursasi, Astuti Yuni; Wiarsih, Wiwin (Nurse Media Journal of Nursing, 2018)
Background: Patients with pulmonary TB experience physical, psychological, social, and spiritual changes, affecting their physical health status. Self-management counseling is an intervention which enhances the physical health status of patients with pulmonary TB.Purpose: This study aimed to identify the effects of self-management counseling on physical health status in patients with pulmonary TB.Methods: This study used a pre and post-test quasi-experimental design with a control group and took place in a hospital in Bogor. The total respondents were 60 patients who were assigned into two groups and recruited using purposive sampling. The counseling was given for four sessions in two weeks for about 60-90 minutes each session. The data were collected using the functional assessment of chronic illness therapy-tuberculosis (FACIT-TB) and analyzed using paired t-test and independent t-test.Results: The result showed that the physical health status in the intervention group increased significantly (MD=8.0, p=0.000) compared to the control group. However, there was no influence of self-management counseling on the improvement of physical health status (MD=3.24, p=0.314).Conclusion: Self-management counseling did not significantly increase the physical health status of pulmonary TB patients. More rigorous studies are needed to investigate the effect of self-management counseling delivered at early treatment on the improvement of physical health status. It is expected that patients can manage their TB symptoms and able to improve their physical health status.